1987
DOI: 10.1007/bf02382574
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis found in the skeletal muscle of common squirrel monkeys

Abstract: ABSTRACT. Abnormally enlarged muscle fiber cells of ring form were incidentally detected in transverse sections of muscles of the common squirrel monkey during microscopic investigation of the composition of muscle fibers. Longitudinal sections showed slender capsule-like cysts in the sarcoplasm. Detailed examination revealed these cysts to be those of Sarcocystis. Among the three types of muscle fiber cells that compose the skeletal muscle, staining with Sudan black B revealed that this parasite selectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported Sarcocystis spp. cysts found in primates (Hernández-Jáuregui et al 1983, Mandour 1969, Karr & Wong 1975, Mehlhorn & Heydorn 1978, Kan et al 1979, Kimura et al 1987, Lane et al 1998, Yang et al 2005) however, to the best of our knowledge, this is the first report of Sarcocystis spp. infection in primates in Brazil.…”
Section: Resultsmentioning
confidence: 73%
“…Several studies have reported Sarcocystis spp. cysts found in primates (Hernández-Jáuregui et al 1983, Mandour 1969, Karr & Wong 1975, Mehlhorn & Heydorn 1978, Kan et al 1979, Kimura et al 1987, Lane et al 1998, Yang et al 2005) however, to the best of our knowledge, this is the first report of Sarcocystis spp. infection in primates in Brazil.…”
Section: Resultsmentioning
confidence: 73%